2009
DOI: 10.1016/j.matbio.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Mice that lack matrix metalloproteinase-9 display delayed wound healing associated with delayed reepithelization and disordered collagen fibrillogenesis

Abstract: Matrix metalloproteinase- (MMP-9) is involved in processes that occur during cutaneous wound healing such as inflammation, matrix remodeling, and epithelialization, To investigate its role in healing, full thickness skin wounds were made in the dorsal region of MMP-9-null and control mice and harvested up to 14 days post wounding. Gross examination and histological and immunohistochemical analysis indicated delayed healing in MMP-9-null mice. Specifically, MMP-9-null wounds displayed compromised reepithelializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
3
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 41 publications
6
108
3
2
Order By: Relevance
“…37 MMP-9, on the other hand, is expressed at the advancing front of the wound epithelium 39 and findings from animal studies evaluating the importance of MMP-9 in wound healing have varied. In MMP-9 knockout mice, accelerated closure of both corneal and skin wounds was reported by Mohan et al, 39 while a delay in re-epithelialization and collagen organization was described by Kyriakides et al 40 In another study, Reiss et al showed that treatment of wounds with active MMP-9 alters the structure of the collagen IV-containing basement membrane and delays reepithelialization. 41 Like MMP-2, abundant active MMP-9 is associated with chronic wounds.…”
Section: Neutrophil-derived Proteasesmentioning
confidence: 88%
“…37 MMP-9, on the other hand, is expressed at the advancing front of the wound epithelium 39 and findings from animal studies evaluating the importance of MMP-9 in wound healing have varied. In MMP-9 knockout mice, accelerated closure of both corneal and skin wounds was reported by Mohan et al, 39 while a delay in re-epithelialization and collagen organization was described by Kyriakides et al 40 In another study, Reiss et al showed that treatment of wounds with active MMP-9 alters the structure of the collagen IV-containing basement membrane and delays reepithelialization. 41 Like MMP-2, abundant active MMP-9 is associated with chronic wounds.…”
Section: Neutrophil-derived Proteasesmentioning
confidence: 88%
“…Mmp8 contributes to the resolution of inflammation, 44 while Mmp9 regulates re-epithelialization and collagen fibril formation during wound repair. 45 Chi3l1 encodes a protein secreted by macrophages that mediates kidney repair by limiting tubular cell death, 46 which may explain the increased cell death with c-fms inhibitor treatment. Collectively, these data clearly indicate the Ly6C int subset plays a paracrine role in repair of the tubular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…They did however produce PDGF-BB, although there is no consensus on whether this factor improves collagen organization [50,51]. Perhaps, MMP-9 expression by hBOEC contributed to collagen organization, since a lack of this MMP results in disordered fibrillogenesis [52]. hBOEC abundantly produce PlGF.…”
Section: Discussionmentioning
confidence: 99%